Behavioral Equilibrium in Economies with Adverse Selection - Esponda, Ignacio (American Economic Review, 2008)
I propose a new solution concept—behavioral equilibrium—to study environments with players who are naive, in the sense that they fail to account for the informational content of other players' actions. I apply the framework to certain adverse selection settings and show that, contrary to the existing literature, the adverse selection problem is exacerbated when naive players fail to account for selection. More generally, the main distinguishing feature of the framework is that, in equilibrium, beliefs about both fundamentals and strategies are jointly restricted. Consequently, whether a behavioral bias may arise or not is determined endogenously in equilibrium. (JEL C70, D82, D83)